Optimal Locating of prisons from the perspective of Passive Defense principles and criteria (Case Study: City of Dogonbadan) - Mostafa Mirabadi; Hosein Nazari; Sadegh Besharatifar (تحقیقات کاربردی علوم جغرافیایی)
One of the key measures in the passive defense debate Critical facilities and facilities not to be hidden, sensitive and important is choosing the right place for them. Given the complexity of the problems Related to choosing the right place for creating custom applications various factors must be considered. The purpose of this study was applied and considering that specific method has been used to identify optimal locations for prison location which is less used, it is considered a development and is, from a methodological point of view, an analytical descriptive research. The method of data gathering is documentary and field. In this research 14 criteria have been used to locate ideal zones for prison establishment. So tools and software like software Arc GIS In order to store, manage, process and analyze data And also the AHP model In the form of software Expert Choice, Depending on the purpose of the study and the type of criteria, Various functions such as distance function, slope function, slope direction function and digital model function Height in software Arc GIS They are used to create maps. The results of locating operations were to identify different zones in the city of Doganbadan Finally, considering the distance dimension and access status of the zones, four optimal zones were introduced. These zones (with total area of ​​5382 square kilometers) surrounded by the village of Talkhab, respectively, of the village of Gardanqalat, around the village of Dezsoleiman and the village of Baba Muhammad.